Textbook of veterinary internal medicine : diseases of the dog and the cat - Ettinger, Stephen J.; Feldman, Edward C. (St. Louis, Mo. : Elsevier Saunders, 2010)
"Now in its 7th edition, this popular, must-have text remains the only encyclopedic resource for veterinary internal medical problems. The internationally acclaimed "gold standard" offers unparalleled coverage of pathophysiology, diagnosis, and treatment of diseases affecting dogs and cats, as well as the latest information on the genome, clinical genomics, euthanasia, innocent heart murmurs, hyperbaric medicine, home prepared and raw diets, obesity, botulism, artificial pacing of the heart, cancer vaccines, and more. The 7th edition combines the convenience of a two-volume printed textbook with the enhanced functionality of a regularly updated Expert Consult website that enables you to electronically search your entire book and study more efficiently. With instant access to the most reliable, up-to-date information available, you'll always be at the forefront of veterinary care!" --Book Jacket.
Grandy -- Peripheral nerve disorders / Christopher L. Mariani -- Disorders of skeletal muscles / Sofia Cerda-Gonzalez -- Neuromuscular junctional disease / Christopher L. Mariani -- Oral and salivary gland disorders / Kendall Taney, Mark M. Smith -- Diseases of the esophagus / Albert E. Jergens -- Host-microbial interactions in gastrointestinal health / Albert E. Jergens -- Diseases of the stomach / Kenneth W. Simpson -- Diseases of the small intestine / Edward J. Hall, Alexander James German -- Diseases off the large intestine / Karin Allenspach -- Rectoanal disease / Melanie Craven -- World Small Aniamal Veterinary Association (WSAVA) guidelines / Claudio Brovida, Jim Rothuizen. General principles in the treatment of liver disease / Jan Rothuizen -- Inflammatory canine heptic disease / Michael D. Willard -- Feline inflammatory livery disease / Andrea M. Harvey, Timonthy J. Gruffydd-Jones -- Hepatic vascular anomalies / Allyson C. Berent, Chick Weisse -- Toxic, metabolic, infectious, and neoplastic liver diseases / Margie A. Scherk, Sharan A. Center -- Diseases of the galbladder and extrahepatic biliary system / Ale Aguirre -- Canine pancreatic disease / Jorg M. Steiner -- Feline pancreatic disease / Robert J. Wasabau -- Growth hormone disorders: acromegally and pituitary dwarfism / Hans S. Kooistra -- Diabetes insipidus / Ad Rijnberk -- Disorders of the parathyroid glands / Edward C. Feldman -- Hypothyroidism / J. Catharine Feldman -- Hypothyroidism / J. Catherine R. Scott-Moncrieff -- Hyperthyroidism / Carmel T. Mooney -- Insulin-secreting islet cell neoplasia / Rebecka S. Hess -- Canine diabetes mellitus / Richard W. Nelson.--Feline diabetes mellitus / Claudia Reusch -- Hyperadrenocorticism in dogs / Carlos Melian, M. Dolores Perez-Alenza, Mark E. Peterson -- Hypercortisolism in cats (Feline Cushing's Syndrom) / Thomas K. Graves -- Hypoadrenocorticism / J. Catharine R. Scott-Moncrieff -- Gastrointestinal endocrine disease / Cynthia R. Ward -- Pheochromocytoma / Melissa Herrera, Richard W. Nelson -- Estrous cycle and breeding management of the healthy bitch / Auke C. Schaefers-Okkens -- Ovarian and estrous cycle abnormalitiies / Autumn P. Davidson, Edward C. Feldman -- Abnormalities in canine pregnancy, parturition, and periparturient period / Catharina Linde Forsberg -- Effect of age at the time of spay or castration on long-term health of dogs and cats / Margaret V. Root Kustritz -- Contraception and pregnancy termination in the dog and cat / Bruce E. Eilts -- Cystic endometrial hyperplasia and pyometria / Luisa Mateus, Bruce E. Eilts -- Canine female infertility / Gary C.W. England.--Vaginal disorders / Beverly J. Purswell -- Breeding soundness examination of the stud dog / Walter R. Threlfall -- Feline reproduction / Anne M. Traas -- Care of the neonate and fading pups / Gary C.W. England -- Clinical approach and laboraory evaluation of renal disease / Stephen P. DiBartola -- Acute uremia / Cathy Langston -- Renal transplantation / Cathy Langston, Lillian R. Aronson -- Chronic kidney disease / David J. Polzin -- Glomerular diseases / Shelly L. Vaden -- Urinary tract infections / Barrak Pressler, Joseph W. Bartges -- Prostatic diseases / Thierry Francey -- Familial renal disease in dogs / George E. Lees -- Renal tubular diseases / Marie E. Kerl. Lower urinary tract disorders in cats / Jodi L. Westropp, C.A. Tony Buffington -- Canine ureteral and lower urinary tract diseases / Larry G. Adams, Harriet M. Syme -- Biomarkers and "omics," / Nancy Emenaker, Jacob Kagan -- Principles of chemotherapy / Angela E. Frimberger -- Practical chemotherapy / Antony S. Moore -- Cancer vaccines and immunotherapy / Philip J. Bergman -- Practical radiation therapy / Alain P. Theon -- Hematropoitic tumors / David M. Vail -- Tumors of the skin / Kenneth M. Rassnick -- Soft-tissue sarcomas / Margaret C. McEntee -- Hemangiosarcoma / Philip J. Bergman -- Bone and joint tumors / Julius M. Liptak -- Mast cell disease / Renita S. Rogers -- Feline injection-site sarcoma / Johannes Hirschberger, Cornelia Huttinger -- Canine and feline histocytic diseases / Peter F. Moore, Verena K. Affolter -- Urogenital and mammary gland tumors / Ruthanne Chun, Laura D. Garrett -- Paraneoplastic syndromes / Carolyn J. Henry.
Includes bibliographical references and indexes.
Keywords: Dogs -- Diseases; Cats -- Diseases; Veterinary internal medicine; Dog Diseases -- diagnosis; Dog Diseases -- therapy; Cat Diseases -- diagnosis; Cat Diseases -- therapy; Veterinary internal medicine